2018
DOI: 10.4111/icu.2018.59.5.305
|View full text |Cite
|
Sign up to set email alerts
|

Predicting trifecta outcomes after robot-assisted nephron-sparing surgery: Beyond the nephrometry score

Abstract: PurposeRENAL nephrometry score (RNS) was devised for deciding the approach for renal tumors. It is increasingly used in predicting perioperative outcomes with variable results. The actual difficulty encountered during surgery depends on a number of other variables. The main purpose of this prospective study was to identify these variables which are not addressed by current RNS.Materials and MethodsForty-nine patients undergoing robotic nephron sparing surgery from January 2015 onward were included. RNS was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…They found the MAP score to be an independent predictor of Trifecta achievement on multivariable analysis, while RENAL score presented a significant association only on univariable analysis [31]. This aspect is supported by the results obtained by Sharma et al [21]. They divided their study population into 2 groups according to the Trifecta status (Trifecta positive and negative patients).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…They found the MAP score to be an independent predictor of Trifecta achievement on multivariable analysis, while RENAL score presented a significant association only on univariable analysis [31]. This aspect is supported by the results obtained by Sharma et al [21]. They divided their study population into 2 groups according to the Trifecta status (Trifecta positive and negative patients).…”
Section: Discussionmentioning
confidence: 73%
“…RENAL and PADUA scores correlated strongly featuring a correlation coefficient of 0.79 which was comparable to our results. Sharma et al [21] compared the RENAL score with a subjective surgeon’s rating and identified a statistically significant correlation. Similarly, Khene et al [29] analyzed a subjective assessment given pre- and postoperatively by the surgeon in comparison with RENAL, PADUA, and the MAP score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations